2002
DOI: 10.1016/s0168-1605(01)00727-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative risk assessment of human infection from Escherichia coli O157 associated with recreational use of animal pasture

Abstract: A quantitative microbial risk assessment incorporating Monte Carlo simulations is described which estimates the probability of Escherichia coli O157 infection of humans by visiting pasture previously grazed by cattle. The risk assessment is performed for a number of scenarios including a variation in the grazing period prior to the human visit, the duration of visit (8-h day or 24-h camp) and the level of E. coli O157 shed by the cattle. Assuming the cattle have been on the field for 28 days, followed directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 29 publications
(42 reference statements)
1
43
2
Order By: Relevance
“…A number of studies have highlighted the potential importance of individual animals shedding high loads of E. coli O157 to within-farm transmission (Matthews et al, 2006;Chase-Topping et al, 2007). It has also been suggested that animals shedding high concentrations increase the risk of human infection and this has been demonstrated in risk assessment simulations for contamination of beef burgers (Cassin et al, 1998) and an environmental outbreak (Strachan et al, 2002). Reduced shedding of E. coli O157 by sheep in the environment during winter periods is not reported in other studies and whether this effect is due to diet or season (length of daylight, temperature) or a combination of these is speculative at this time.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have highlighted the potential importance of individual animals shedding high loads of E. coli O157 to within-farm transmission (Matthews et al, 2006;Chase-Topping et al, 2007). It has also been suggested that animals shedding high concentrations increase the risk of human infection and this has been demonstrated in risk assessment simulations for contamination of beef burgers (Cassin et al, 1998) and an environmental outbreak (Strachan et al, 2002). Reduced shedding of E. coli O157 by sheep in the environment during winter periods is not reported in other studies and whether this effect is due to diet or season (length of daylight, temperature) or a combination of these is speculative at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli O157 from eating beef burgers21 and from recreational use of animal pasture25, Cryptosporidium parvum in drinking water26 and Listeria monocytogenes in smoked salmon and trout27. A number of studies have been carried out to determine the levels of Anisakis spp.…”
mentioning
confidence: 99%
“…Studies utilizing quantitative risk assessments have indicated that any reduction in the numbers of known pathogens throughout the processing chain will assist in reducing the negative impact on the consumer (Strachan, Dunn, & Ogden, 2002). In the case of S. Sofia there is little information on the level of this organism in poultry and in conjunction with this serovars low level of virulence this information may play a role in future risk assessments.…”
Section: Prevalence and Enumeration In Poultrymentioning
confidence: 99%